Development Peculiarities of Bean Anthracnose and Protective Measures - Avagyan, G. V. (ՀԱԱՀ հիմնադրամ)
The life cycle of Colletotrichum lindemuthianum fungus, susceptibility of Armenian bean varieties to anthracnose disease, as well as its development dynamics have been investigated in conditions of Lor community in Aremenia. Preventive measures have reduced the winter stock of pathogen infection and intensity of the disease development, while double application of Quadris and Revus Top fungicides during the vegetation period suppressed the development of anthracnose by 86.3-88.6 % and 91.6-92.4 %, respectively, as compared to the recorded indices in the control variant. Thus, the recommended fungicides can be used alternately to combat bean anthracnose.
Keywords: Agronomy and Agroecology